Oxytocin Massage on Pain Levels and Breast Milk Production in Post Cesarean Section (Case Study) - Chidani, Mallika Kharisma; Desmarnita, Ulty (Center of Excellent (Pusat Unggulan Iptek), 2024)
Post cesarean section (CS) is a physiological condition that occurs in women who give birth via cesarean section or surgery. The changes include pain, uterine involution, breastfeeding (ASI) production, and psychological adjustments.. According to research, 20-80% of post CS patients experience moderate to severe pain that is inadequately managed. In Indonesia, this occurs at a rate of 30-80%. The effective breastfeeding rate in Indonesia is 55.5%, which does not yet meet the national target of 80%. Given the magnitude of these issues, the author aims to describe the influence of oxytocin massage application on pain levels and ASI production in post CS patients through this scientific work. The methodology used is a case study involving patients Mrs. L on their first day post CS. The intervention was applied from the second to the third day post CS, twice daily. The results of this application show that oxytocin massage can reduce pain from a scale of 7 to 3 and increase breast milk production, with a cumulative increase from no milk output to more than 50 cc.. It is hoped that the application of evidence-based nursing: oxytocin massage can be implemented as a standard intervention for post CS patients in hospitals.